THE EFFECT OF ELDERLY EXERCISES ON REDUCING PAIN IN THE ELDERLY AT THE AL-ISLAH ELDERLY CENTER - Enos Umbu mada Hahar; Sih Ageng Lumadi; Sismala Harningtyas (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Elderly or old age is the final stage of human life development, starting from the age of 60 years and above. The elderly experience a decrease in the ability of the body's organs to repair themselves or change or maintain normal function. Gymnastics for the elderly is light exercise that can be done anywhere, and is a sport that is not included in the heavy exercise category, so it can be applied to the elderly. Objective: to determine the effect of exercise on reducing pain in the elderly at the Al-ishlah elderly home. Method: The research design used was pre-experimental using one class pre test-post test design. The total sample of 22 respondents was included in this research. The Wilcoxon test was used in this research with the SPSS program. Results: test results p value = 0.000. This result shows a significant value smaller than the specified value, namely 0.05 (p≤0.05). Based on these results, Ha was accepted and Ho was rejected, so it was concluded that Ha was accepted, meaning that there was an influence of elderly exercise on reducing pain in the elderly at the Al-Islah Elderly Home. Conclusion: There is an influence of elderly exercise on reducing pain in the elderly with a pain score scale of mild, moderate and severe